As personagens de cor na Literatura Brasileira e em "Os Tambores de São Luís" de Josué Montello - Santos, Maria Rita (1980)
In this brief Brazilian Literature research we seek to detect and analyze the inter-ethnic relations and participation of black, either as subject or as a literary producer in the plans of poetry and novelistic fiction. The question of color prejudice is so inevitable, being emphasized more persistence and particularity in reading The Drums of St. Louis Joshua Montello, novel that, as we try to show is fairly representative in the context of regional and national slavery.